Selection of the motivation strategy for employees in the mining industry using the GRA method - Janovac Tatjana; Karabašević Darjan; Maksimović Mlađan; Radanov Pavle (Mining and Metallurgy Engineering Bor, 2018)
Human resources in an organization are one of the most important resources. Their motivation and satisfaction is a tool in achieving and retaining the organization's competitive advantage. The motivation of employees motivation is one of the main goals of the human resource management, since it has a direct impact on the performance itself, productivity of employees and the overall organizational performance. The aim of this paper is to propose an approach to the selection of motivation strategy for employees based on the multi-criteria decision-making. The approach is based on the GRA method, i.e. gray relational analysis. An illustrative numerical example was carried out in this paper. The proposed approach, based on the gray relational analysis, was successfully applied for selection the motivation strategy for employees in the mining industry.